Differences in Candida Albicans hydrophobicity and biofilm formation between thermoplastic nylon and polyether-ether-ketone denture base materials - Ismiyati, Titik (Majalah Kedokteran Gigi Indonesia, 2022)
Polyetheretherketone (PEEK) and thermoplastics nylon are extensively composed as an alternative material for removable denture base. The primary difference between the two materials is associated with water absorption properties. The two materials interact with saliva and microorganisms during application in the oral cavity. Candida is predominantly reported in the cavity. The microorganism is distinguished by its hydrophobicity and ability to form biofilms. The objective of this study was to determine the differences between thermoplastic nylon and polyether-ether-ketone as removable denture materials in terms of hydrophobicity and Candida albicans biofilms. It is a laboratory experiment using 20 5 x 2 mm samples for the hydrophobicity test and Candida albicans biofilm. The hydrophobicity test was performed by determining the contact angle with a Goniometer and the WinDrop++ software. The biofilm test samples were divided into 4 groups, encompassing PEG 5% (negative control), PEEK treatment, thermoplastics nylon, and 0.12% chlorhexidine (control positive). The microdilution method was employed to examine biofilm formation. The results of the study were interpreted, and the data were analyzed by employing the t test. The research discovered significant differences in biofilm formation, large contact angle on PEEK and thermoplastics nylon (p < 0.05). Biofilm formation on thermoplastics is significantly larger than PEEK (p < 0.05). In conclusion, the contact angles of PEEK and thermoplastic nylon are incorporated in the partially wetted. Polyetheretherketone is involved in the non-producers of biofilms while thermoplastic nylon is categorized in of weak biofilm formers.